Aura framing and fan behavioral intentions: a quantitative case study of Harra’s digital branding strategy - Ahmad Budi Sulistioyuwono; Mulyadi Muchtiar; Erlangga Rahmini; Herman S Soegoto; Agus Riyanto (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2026)
This study examines the influence of aura framing on fan behavioral intentions in the context of the Indonesian pop band Harra. The research aims to analyze how visual content affects fan engagement and behavioral responses in digital media. The study employed a quantitative explanatory case study design integrating primary and secondary data. Primary data were collected through an online survey involving 112 fans, while secondary data were obtained from Google Analytics to evaluate engagement metrics from Harra’s Instagram posts. The study investigates the effects of Visual Liveness, Visual Authenticity, and Visual Emotionality on fan behavioral intentions, including willingness to buy, membership continuance intention, and electronic word-of-mouth intention. Data analysis was conducted using validity and reliability testing followed by multiple linear regression analysis. The findings reveal that all dimensions of visual aura significantly influence fan behavioral intentions, with Visual Authenticity emerging as the strongest predictor. In addition, digital engagement increased following the release of Harra’s single. These findings indicate that emotionally authentic and relatable visual content plays an important role in strengthening fan loyalty and online engagement. Theoretically, this study contributes to the development of digital branding studies by extending the concept of aura framing as a mechanism for fostering emotional closeness and fan loyalty through visual communication. Practically, the study provides insights for independent musicians and creative industry practitioners in developing authentic and emotionally resonant visual branding strategies to strengthen long-term audience engagement.